Altered Serum Amino Acid and Acylcarnitine Profiles in Hyperinsulinemic Hypoglycemia and Ketotic Hypoglycemia - Xu, Zhen-Ran; Zhu, Xiao-Yi; Lu, Wei; Sun, Wei-Hua; Cheng, Ruo-Qian; Ni, Jin-Wen; Xi, Li; Hussain, Khalid; Luo, Fei-Hong; Zhang, Miao-Ying (Frontiers in Endocrinology, 2020)
Background: Congenital hyperinsulinemic hypoglycemia (HH) is a rare metabolic disease. Suppressed free fat acids, β-hydroxybutyrate levels and altered serum branched-chain amino acid were found during the acute course of HH. While scarce studies have described the overall secondary metabolic spectrum changes. We thus investigate the metabolic profiles in HH and ketotic hypoglycemia children and analyze their distinguished features. Methods: A total of 97 hypoglycemia children, 74 with hyperinsulinemic hypoglycemia and 23 with ketotic hypoglycemia, and 170 euglycemia control subjects were studied retrospectively. Clinical and biochemical data were collected. The fasting spectra of amino acids and acylcarnitines were determined by liquid chromatography tandem mass spectrometry. The serum insulin and fatty acid concentrations during standardized fasting tests of hypoglycemia patients were also collected. Receiver operating characteristic curve analysis was performed to screen potential biomarkers. Results: Among the spectra of amino acids, blood valine (p < 0.001), arginine (p < 0.001), threonine (p = 0.001), glutamate (p = 0.002), methionine (p = 0.005), ornithine (p = 0.008), leucine (p = 0.014), alanine (p = 0.017), proline (p = 0.031), citrulline (p = 0.042), aspartate (p = 0.046), and glycine (p = 0.048) levels differed significantly among the three groups. Significantly decreased levels of long- (C14:1, p < 0.001; C18, p < 0.001), medium- (C8, p < 0.001; C10, p < 0.001; C10:1, p < 0.001) and short-chain (C4-OH, p < 0.001; C5OH, p < 0.001) acylcarnitines were found in the hyperinsulinemic hypoglycemia group. Hyperinsulinemic hypoglycemia children with focal lesions and diffuse lesions had similar amino acid and acylcarnitine spectra. Threonine/C10:1 > 440 had a sensitivity of 81.1 % and a specificity of 81.8% for the diagnosis of hyperinsulinemic hypoglycemia. Conclusions: We found relatively decreased levels of serum amino acids and acylcarnitines in hyperinsulinemic hypoglycemia children, indicating suppressed fatty acid oxidation and proteolysis in hyperinsulinemic hypoglycemia.